Land Use Decision Using Soil Indices and Fuzzy Inference System in AL-Khamisiyah - Hatem, Amal J.; Zaeen, Ahmed Asaad; Abbas, Heba Kh.; Raheem, Mustafa A. (Iraqi Journal of Science, 2026)
The selection of the most suitable land for cultivating a particular crop is one of the major problems facing the Ministry of Agriculture in general and farmers in particular, and this suitability for cultivation depends on many factors (natural and human), including soil type. This research used indicators, remote sensing, and spatial modeling to solve this problem. The method of band rationing was applied to calculate the salinity index (SI) and the Normalized Multi-Drought Index (NMDI) as a pre-processing for agricultural decision-making in specific areas in southern Iraq (Dhi Qar, Al-Khamisiyah), using the Landsat-8 satellite image of this area. Maximum likelihood classification was used to classify the study area into multiple classes. The soil was classified in a study area using a fuzzy inference system (FIS) to determine suitability for growing different types of crops according to the values of the salinity index and the multiple drought index measured for each crop. The results of the study showed that Al-Khamisiyah land is valid and suitable for the cultivation of specific crops (onions, lettuce, cabbage, cucumbers, celery, guava, and cowpeas) with an area of ​​946,541,700 m2 of the studied area, while it is not suitable for the cultivation of other crops namely pepper and beets.